High lactic acid levels in the brain contribute to the generation of focal slowing on the electroencephalogram - Chegodaev, Dmitry Alexandrovich; Pavlova, Polina Alekseevna (Frontiers in Neurology, 2024)
Focal slowing on the EEG is often associated with structural pathology of the brain. Despite the clinical significance of focal slowing, the actual electrochemical mechanisms underlying this EEG phenomenon are still poorly understood. This paper briefly reviews the role of lactate in the pathogenesis of brain disorders that are primarily related to focal EEG slowing. An attempt is made to trace the hypothetical link between this EEG pattern and focal cerebral tissue lactacidosis.